Co-occurrence of autoimmune haemolytic anaemia and β-thalassaemia major in an infant: a case report and updated pathogenic insight - Idris, Faridah; Abd Rahman, Siti Umairah; Mohd Tohit, Eusni Rahayu; Stephen, Claudia Cassandra; Mohamed, Rashidah; Wan Alkamar Shah, Wan Nurul Husna (Faculty of Medicine and Health Sciences, UPM, 2024)
Thalassaemia, a common inherited blood disorder, involves defective globin production leading to premature erythrocyte destruction. Autoimmune haemolytic anaemia (AIHA), a rare complication in thalassaemia, is characterised by autoantibody production against erythrocytes. We present a case of a 7-month-old boy diagnosed with β-thalassaemia major (BTM), complicated by AIHA six weeks after initiating blood transfusions. Despite daily transfusions and oral Prednisolone, the haemoglobin (Hb) level dropped to a life-threatening level (2.5g/dl). High-dose IV Methylprednisolone and Rituximab were administered, resulting in Hb improvement to 11.9 g/dL. AIHA resolution was indicated by negative C3d and reduced IgG on repeated testing. Recognition of AIHA in BTM is vital for effective management, including immunosuppressive therapy, leucodepleted transfusions, and potential splenectomy or haematopoietic stem cell transplant. Early intervention is crucial to reduce the mortality associated with AIHA in children.